2019
DOI: 10.1038/s41598-019-50777-x
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Magnesium- and Silicon-modified Hydroxyapatites by Microwave-Assisted Method

Abstract: Nanopowders of hydroxyapatite (HA), modified by magnesium (MgHA) and by silicon (SiHA) were obtained by liquid-phase microwave synthesis method. X-ray diffraction and IR spectroscopy results showed that Mg2+ and SiO44− ions were present in the synthesized products both as secondary phases and as part of the HA phase. Whitlockite was found in the magnesium-modified HA (MgHA) and larnite was found in the silicon-modified HA (SiHA); ion substitution for both materials resulted in solid solutions. In the synthesiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 29 publications
(21 reference statements)
2
15
0
2
Order By: Relevance
“…in Figure 10, all scaffolds determined a significant increase in ALP activity after 14 and days in BMSC incubated in basal medium with respect to control cells, whereas afte days, no significant change was detected. However, ALP activity reached maximum v ues after 14 days of BMSC seeding on the scaffolds, while after 21 days, ALP valu showed a decrease while remaining higher than in control cells.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…in Figure 10, all scaffolds determined a significant increase in ALP activity after 14 and days in BMSC incubated in basal medium with respect to control cells, whereas afte days, no significant change was detected. However, ALP activity reached maximum v ues after 14 days of BMSC seeding on the scaffolds, while after 21 days, ALP valu showed a decrease while remaining higher than in control cells.…”
Section: Resultsmentioning
confidence: 90%
“…Kim et al reported enhanced biocompatibility of magnesium-and silicon-substituted sintered HA and suggested that it could be a useful material for bone augmentation [11]. The processes of bioresorption can be controlled by the substitution of Mg 2+ and SiO 4 4− ions into the structure of HA, and it also accelerates the formation of a new apatite layer on the surface of the material [12][13][14]. Magnesium also plays an important role in mediating cell-extracellular matrix interaction, thus the incorporation of Mg 2+ in the HA crystal structure can facilitate new and dense bone formation as a result of the stimulated growth of osteoblasts [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…(Bose et al, 2013 , Hoppe et al, 2011 ). Starting from this evidence, more scientific works reported the fabrication of ions doped apatite (Aina et al, 2012 ; Padmanabhan et al, 2014 ; Scalera et al, 2017 ; Rasskazova et al, 2019 ; Scalera et al, 2020 ). Among ions found in the natural bone tissues, magnesium and silicon play an important role in the development of new bone tissue, allowing the control of bioresorption and facilitating the biomineralization and the formation of bone stock on the surface of the material (Landi et al, 2008 ; Munir et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…As the amount of Mg ion increases, the C3S peaks shift to a higher diffraction angle. These peak shift towards higher 2θ indicates a reducing d-spacing because the ionic radius of Mg 2+ (0.74 Å) is smaller than Ca 2+ (1.04 Å) [47]. Also, in Mg-CSC (Mg = 1 to 5%) specimens, the C2S peaks were formed, and these peaks present no shift with different contents of Mg ion.…”
Section: Discussionmentioning
confidence: 93%